IL-21 and IL-12 Inhibit Differentiation of Treg and TH17 Cells and Enhance Cytotoxicity of Peripheral Blood Mononuclear Cells in Patients With Cervical Cancer. Issue 9 (1st November 2011) - Tian, Yongju; Yuan, Cunzhong; Ma, Daoxin; Zhang, Yan; Liu, Yi; Zhang, Wenjing; Hou, Fei; Cui, Baoxia
Abstract : Objectives: Interleukin 21 (IL-21) and IL-12 have been known to be effective antitumor agents. In this study, we evaluated whether IL-21 in combination with IL-12 could enhance the cytotoxicity of peripheral blood mononuclear cells (PBMCs) in patients with cervical intraepithelial neoplasia III and cervical cancer. Methods: Peripheral blood mononuclear cells were isolated from peripheral blood of cervical intraepithelial neoplasia III patients (n = 17) and cervical cancer patients (n = 18). Peripheral blood mononuclear cells were cultured with IL-2 in low concentration as control group. Interleukin 2–stimulated PBMCs were cocultured with anti–human IL-21 neutralizing antibody, IL-21 alone, IL-12 alone, and IL-21 plus IL-12, respectively, as test groups. The cytotoxicity of PBMCs against SiHa tumor cells was examined by lactate dehydrogenase released assay. CD4 + CD25 + FOXP3 + T regulatory (Treg) cells and CD4 + IL-17A + T helper 17 (TH 17) cells were analyzed by flow cytometry. Proliferation and apoptosis were detected by CCK-8 (cell counting kit 8) assay and flow cytometry, respectively. Results: Compared with controls, IL-21 and IL-12 significantly elevated PBMC cytotoxicity against SiHa cells. Moreover, IL-21 plus IL-12 significantly elevated PBMC cytotoxicity in comparison to IL-21 alone and IL-12 alone. We also found that IL-21 plus IL-12 significantly decreased Treg and TH 17 cell proportion in comparison to controls. Notably, IL-21 plus IL-12 significantly decreased TH 17 cell proportion in comparison to IL-21 alone. Both IL-21 and IL-12 significantly decreased the apoptosis rate of PBMCs, whereas neither IL-21 nor IL-12 had significant effect on PBMC proliferation. Conclusions: The combination of IL-21 and IL-12 could efficiently stimulate PBMCs with cytotoxicity against SiHa cells, and the possible mechanisms may be due to down-regulated Treg and TH 17 cell differentiation.